Força muscular respiratória, qualidade de vida e modulação autonômica da frequência cardíaca na distrofia miotônica - Araújo, Thaise Lucena (2009)
Background: The myotonic dystrophy (MD) is a multisystem neuromuscular disease that can affect the respiratory muscles and heart function, and cause impairment in quality of life. Objectives: Investigate the changes in respiratory muscle strength, health-related quality of life (HRQoL) and autonomic modulation heart rate (HR) in patients with MD. Methods: Twenty-three patients performed assessment of pulmonary function, sniff nasal inspiratory pressure (SNIP), the maximal inspiratory (MIP) and expiratory (MEP) pressure, and of HRQoL (SF-36 questionnaire). Of these patients, 17 underwent assessment of heart rate variability (HRV) at rest, in the supine and seated positions. Results: The values of respiratory muscle strength were 64, 70 and 80% of predicted for MEP, MIP, and SNIP, respectively. Significant differences were found in the SF-36 domains of physical functioning (58.7 ± 31,4 vs. 84.5 ± 23, p<0.01) and physical problems (43.4 ± 35.2 vs. 81.2 ± 34, p<0.001) when patients were compared with the reference values. Single linear regression analysis demonstrated that MIP explains 29% of the variance in physical functioning, 18% of physical problems and 20% of vitality. The HRV showed that from supine position to seated, HF decreased (0.43 x 0.30), and LF (0.57 x 0.70) and the LF/HF ratio (1.28 x 2.22) increased (p< 0.05). Compared to healthy persons, LF was lower in both male patients (2.68 x 2.99) and women (2.31 x 2.79) (p< 0.05). LF / HF ratio and LF were higher in men (5.52 x 1.5 and 0.8 x 0.6, p <0.05) and AF in women (0.43 x 0.21) (p< 0.05). There was positive correlation between the time of diagnosis and LF / HF ratio (r = 0.7, p <0.01). Conclusions: The expiratory muscle strength was reduced. The HRQoL was more impaired on the physical aspects and partly influenced by changes in inspiratory muscle strength. The HRV showed that may be sympathetic dysfunction in autonomic modulation of HR, although with normal adjustment of autonomic modulation during the change of posture. The parasympathetic modulation is higher in female patients and sympathetic tends to increase in patients with longer diagnosis